Financial Stability and Economic Growth Nexus: Evidence from Sub-Saharan Africa using Panel Data - Ahulu, Helena; MacCarthy, John; Muda, Paul (International Journal of Economics and Financial Issues, 2021)
This paper examines the effect of financial stability on the economic growth of countries in Sub-Saharan Africa using the World Development Indicators Data. To select the appropriate model best fits for the data, the Hausman test was used to select Random Effect Estimator over Fixed Effect Estimator to assess the relationship between the variables. Panel data was collected on Sub-Saharan Africa countries from 2010 to 2019 to predict the effect of financial stability on economic growth. The paper revealed that financial stability accounted for 71.8% of the variation of a country’s economic growth for the period other things being equal. It recommends that financial regulators within Sub-Saharan African should provide prudential policies aim at attaining higher economic growth should target both monetary and fiscal policies as well market discipline. Keywords: Sub-Saharan African, economic growth, financial stability, panel data, Fixed effects estimator JEL Classifications: E50, E58, F43, O47 DOI: https://doi.org/10.32479/ijefi.11407